Magnetic fields are causing small, but significant changes of the radiochromic EBT3 film response to 6 MV photons. (31st January 2018) - Delfs, Björn; Schoenfeld, Andreas A; Poppinga, Daniela; Kapsch, Ralf-Peter; Jiang, Ping; Harder, Dietrich; Poppe, Björn; Looe, Hui Khee
Abstract: The optical density ( OD ) of EBT3 radiochromic films (Ashland Specialty Ingredients, Bridgewater, NJ, USA) exposed to absorbed doses to water up to D   =  20 Gy in magnetic fields of B   =  0.35 and 1.42 T was measured in the three colour channels of an Epson Expression 10000XL flatbed scanner. A 7 cm wide water phantom with fixed film holder was placed between the pole shoes of a constant-current electromagnet with variable field strength and was irradiated by a 6 MV photon beam whose axis was directed at right angles with the field lines. The doses at the film position at water depth 5 cm were measured with a calibrated ionization chamber when the magnet was switched off and were converted to the doses in presence of the magnetic field via the monitor units and by a Monte Carlo-calculated correction accounting for the slight change of the depth dose curves in magnetic fields. In the presence of the 0.35 and 1.42 T fields small negative changes of the OD values at given absorbed doses to water occurred and just significantly exceeded the uncertainty margin given by the stochastic and the uncorrected systematic deviations. This change can be described by a  +2.1% change of the dose values needed to produce a given optical density in the presence of a 1.42 T field. The thereby modified OD versus D function remained unchanged irrespective of whether the original short film side—the preference direction of the monomer crystals of the film—was directed parallel or orthogonal to the magnetic field. The 'orientation effect', the difference between the optical densities measured in the 'portrait' or 'landscape' film positions on the scanner bed caused by the reflection of polarised light in the scanner's mirror system, remained unaltered after EBT3 film exposure in magnetic fields. An independent optical bench investigation of EBT3 films exposed to doses of 10 and 20 Gy at 0.35 and 1.42 T showed that the direction of the electric vector of polarised light experiencing the largest transmission through EBT3 films remained unaltered after film exposure in the magnetic fields. The observed small modification of the OD versus D curve of the radiochromic film EBT3 in the range up to 20 Gy and 1.42 T, hardly exceeding the experimental uncertainty margin, numerically confirms other recent studies on EBT3 film. A stronger magnetic field effect had been observed with the previous product EBT2 exposed to 60 Co gamma radiation at 0.35 T.